How digital support and digital competence influence digital resilience of college students in an online learning environment - Pan, Fangfang; Zhu, Guangxing (Frontiers in Psychiatry, 2025)
With the deep integration of digital technology and education, online learning has become a primary learning method for college students. However, issues such as information overload, technological risks, and a lack of presence frequently arise, intensifying the information cocoon phenomenon, which exposes students to more uncertainties and challenges in learning process, making it urgent for them to possess digital resilience to cope effectively. The study conducted a questionnaire survey among 4894 college students from China to explore the impact mechanism of digital support and digital competence on digital resilience. SPSS 27.0 and Amos 27.0 were used to perform reliability, validity and discriminant validity tests, descriptive statistics, and structural equation modeling. Meanwhile, Mplus 8.0 was applied for multiple-indicator and multiple-cause analysis. The research results indicate that both digital support and digital competence significantly influence digital resilience. Meanwhile, interpersonal interaction, including social and academic interactions, act as mediators between digital support, digital competence and digital resilience. Furthermore, the impact of digital competence on interpersonal interaction and digital resilience is considerably higher than that of digital support. The results of multiple-indicator and multiple-cause indicate that after adding covariates, the action paths and directions between the variables remain unchanged, with only slight changes in coefficients. It proves that the model constructed has good robustness. The study reveals the formation mechanism of college students’ digital resilience in the online learning environment. It also provides empirical evidence and practical paths for enhancing students’ technical adaptability, risk response ability and continuous learning ability in the digital environment.